2018
DOI: 10.1038/s41598-018-25835-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma lipoprotein(a) levels were associated with increased risk of cardiovascular events in Chinese patients with stable coronary artery disease

Abstract: Recent studies have suggested that lipoprotein(a) [Lp(a)] is associated with cardiovascular disease (CVD). However, the contribution of Lp(a) to residual risk of CVD has not been determined in Chinese populations. We conducted a prospective study to evaluate the association between Lp(a) and the risk of major adverse cardiovascular events (MACEs) in patients with stable coronary artery disease (CAD) who received optimal medication treatment (OMT). The study enrolled 1602 patients with stable CAD from 5 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…As described in previous study [ 17 ], patients were diagnosed with stable CAD if they presented with one of the following clinical phenotypes as a result of significant coronary artery atherosclerotic stenosis: 1) stable angina: chest pain precipitated by physical activity that remits with rest; 2) ischemic cardiomyopathy: cardiomyopathy caused by the atherosclerotic narrowing of coronary arteries; 3) latent coronary artery disease: disease characterized by myocardial ischemia and coronary stenosis that are identifiable by medical tests but not with apparent clinical symptoms [ 18 , 19 ]. Contrarily, acute coronary syndrome (including unstable angina and myocardial infarction), vasospastic angina, and microvascular angina were not considered into the scope of stable CAD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described in previous study [ 17 ], patients were diagnosed with stable CAD if they presented with one of the following clinical phenotypes as a result of significant coronary artery atherosclerotic stenosis: 1) stable angina: chest pain precipitated by physical activity that remits with rest; 2) ischemic cardiomyopathy: cardiomyopathy caused by the atherosclerotic narrowing of coronary arteries; 3) latent coronary artery disease: disease characterized by myocardial ischemia and coronary stenosis that are identifiable by medical tests but not with apparent clinical symptoms [ 18 , 19 ]. Contrarily, acute coronary syndrome (including unstable angina and myocardial infarction), vasospastic angina, and microvascular angina were not considered into the scope of stable CAD.…”
Section: Methodsmentioning
confidence: 99%
“…As described in our previous study [ 17 ], blood samples were drawn by venipuncture after at least 10 h of overnight fasting. The blood specimens were processed and assessed at the central laboratory in each hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that in homozygous Plasminogen Activator Inhibitor-1 4G/5G Polymorphism; levels of Lipoprotein (a) are increased. Levels greater than 30 mg/dl are associated with atherosclerosis risk as well as ischemic strokes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Specific blood chemistries included fasting serum BAs, glucose and lipids, as well as liver and renal function tests. As previously described [22,23], blood samples were drawn by venipuncture after overnight fasting. The blood specimens were processed and measured at the central laboratory in The Second Xiangya hospital, which is standardized and certified.…”
Section: Data Collectionmentioning
confidence: 99%